Home Network Basis: Transmission Environments and Wired/Wireless Protocols - Chen, Walter (Pearson, 2003)
This complete technical guide to home network media, protocols, and implementation is the first systematic technical guide to all leading transmission media and communication protocols for in-home networking. Using detailed simulation techniques provided as MATLAB files and SIMULINK models (downloadable from the companion website), Walter Y. Chen covers the technical challenges and implementation of twisted-pair telephone wiring, coax, powerline, and RF transmission. Next, Chen thoroughly reviews each leading communications protocol: Ethernet, HomePNA 1.0/2.0, FireWire, X-10, CEBus, HomePlug, Wireless LAN, and HomeRF. Finally, he covers today's leading mechanisms and protocols for linking the Internet with home networks. Coverage includes: Transmission potentials for each medium, including channel and noise models, and channel capacity calculation Key features of each standard, with corresponding implementation approaches Standardized transmission protocols, corresponding transceiver structures, and performance estimates Home network topologies and interconnection protocols, including Peer-to-Peer, NAT, and MAC Bridging.